CHALLENGES IN IMPLEMENTING INCLUSIVE EDUCATION IN AN INDONESIAN KINDERGARTEN; A CASE STUDY - Pasiningsih, Pasiningsih (THUFULA, 2024)
This study is a case study exploring the challenges of implementing inclusive education at Star Kindergarten, a private kindergarten in Yogyakarta, Indonesia. Data collection was conducted through observations and interviews with two teachers who have students with disabilities in their classes. The data were then analyzed using the three-step analysis method recommended by Miles and Huberman. The findings indicate that both students and teachers have positive attitudes towards inclusive education. However, three challenges may hinder the implementation of inclusive education at Star Kindergarten, despite the school serving children from upper-middle-class socioeconomic backgrounds. These challenges are the teachers’ lack of knowledge due to not coming from early childhood education programs, insufficient training provided by the school, and minimal parental support. Professional training for teachers and parent-school collaboration is necessary to support the implementation of inclusive education in kindergarten.